Pemetaan Tipologi Pengelolaan Sampah Secara Partisipatif di RW 05 Kelurahan Lebak Siliwangi Kota Bandung - Rahma Dewi; Lely Syiddatul Akliyah; Rose Fatmadewi; Hilwati Hindersah; Muhammad Zharfan Nafis’aly; Ananda Muhammad Raihan; Sophi Ayni Putri Kurniawan (Universitas Muhammadiyah Surakarta, 2025)
Community awareness regarding waste sorting and processing in RW 05, Lebak Siliwangi Subdistrict remains relatively low. This condition is primarily attributed to a top-down management approach and limited citizen involvement in planning and implementation processes. To foster active participation, a participatory and context-sensitive approach is essential. This activity aims to map the potential and challenges of waste management and facilitate the development of citizen-based programs. The methods employed include Focus Group Discussions (FGD), Geographic Information System (GIS)-based mapping, and classification into five management typologies based on a combination of educational status, sorting practices, and waste processing behavior. The findings reveal that out of 121 households, 67.8% have received education on waste management. However, only 25.6% practice waste sorting, and a mere 4.1% engage in waste processing. The majority (42.9%) of residents are educated but have yet to adopt sorting or processing practices, indicating the need for sustainable strategies to encourage independent waste management behaviors. This initiative produced several outputs, including thematic waste management maps, scientific publications, video documentation, and educational materials. These outputs support the ongoing efforts to achieve a Zero Waste Area status through enhanced community capacity and participation.